Effect of Water Stress on Biochemical Metabolites in Fenugreek (Trigonella Foenum-Graecum L.) Genotypes - Meena, Sonam; Meena, Ajit Kumar; Meena, Savita; Meena, Deshraj (Research Parks Publishing LLC, 2023)
A field experiment was conducted at Agronomy farm, S.K.N. Collage of Agriculture, Jobner during Rabi season 2014-2015 to investigate “Biochemical changes in fenugreek (Trigonella foenum graecum L.) genotypes under water stress” using Five genotypes of fenugreek (UM-100,UM-112,UM-124,UM-134,UM-140). The significant increment observed in proline content, Glycine betaine content and Peroxidase activity due to water stress at both the stages. A Reduction in the content of total chlorophyll and GSH in stressed plants of all genotypes was recorded at both stages. Significant reductions in total carotenoids content were found in all the genotypes at 65 DAS under water stress conditions. The MDA values in stressed plants were found higher over respective controls at both stages in all the genotypes.